2010
DOI: 10.1111/j.1476-5829.2009.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor is expressed in normal canine mammary gland and benign adenomas but decreased in metastatic canine mammary carcinomas similar to human breast cancer

Abstract: Insulin receptor (INSR) or insulin-like growth factor (IGF) signalling is speculated to be involved in mammary tumour development. Expression levels of members of the insulin receptor family (INSR, IGF1R, IGF2R, GHR) and their ligands IGF1and IGF2 were quantified in macro-and microdissected tissue samples of normal canine mammary gland, adenomas, carcinomas and their lymph node metastases to evaluate their potential impact on the carcinogenesis of canine mammary tumours. Normal mammary gland and adenomas had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Of interest qPCR analyses confirmed the differences in mRNA expression levels in metastatic and non-metastatic carcinomas although the fold change in expression difference consistently lower in the qPCR assays when compared with microarray assays for all eight genes analyzed. The eight genes, AURKA, ALOX12, BMP6, ERBB4, HEPACAM2, IGFR2, RAD51, TGFBR3 , were selected due to their description in the literature on canine mammary tumors before[17,21-24,51]. Their gene expression has been described metastatic carcinomas, metastases, adenomas and normal mammary gland and these studies showed a similar tendency of changes in gene expression between benign and malignant canine mammary tissue types[17,21-24,51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of interest qPCR analyses confirmed the differences in mRNA expression levels in metastatic and non-metastatic carcinomas although the fold change in expression difference consistently lower in the qPCR assays when compared with microarray assays for all eight genes analyzed. The eight genes, AURKA, ALOX12, BMP6, ERBB4, HEPACAM2, IGFR2, RAD51, TGFBR3 , were selected due to their description in the literature on canine mammary tumors before[17,21-24,51]. Their gene expression has been described metastatic carcinomas, metastases, adenomas and normal mammary gland and these studies showed a similar tendency of changes in gene expression between benign and malignant canine mammary tissue types[17,21-24,51].…”
Section: Discussionmentioning
confidence: 99%
“…The eight genes, AURKA, ALOX12, BMP6, ERBB4, HEPACAM2, IGFR2, RAD51, TGFBR3 , were selected due to their description in the literature on canine mammary tumors before[17,21-24,51]. Their gene expression has been described metastatic carcinomas, metastases, adenomas and normal mammary gland and these studies showed a similar tendency of changes in gene expression between benign and malignant canine mammary tissue types[17,21-24,51]. Of note, a comparison of the proteome of the same subset of tumours did not identify similar proteins[52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies show that the expression of IGF-II and IGF2R is strongly decreased in carcinomas and metastatic breast cancer, but increased in normal gland and adenomas (23). M6P/IGF2R reduces tumorigenicity and invasive potential of HCC, but knockdown of M6P/IGF2R enhances cell motility and invasiveness (24).…”
Section: Discussionmentioning
confidence: 99%
“…A similar decreased receptor expression with increasing malignancy has been described in several canine tumors before, including the serotonin receptor on canine MCT and several growth factor receptors on metastatic canine mammary carcinomas. 8,[20][21][22] This down-regulation of mostly proliferative but also inhibitory receptors therefore seems to be a common mechanism in canine tumors and reflects the increasing independency of malignant tumors from external proliferation stimuli when compared with benign tumor variants or nonneoplastic cells.…”
Section: Discussionmentioning
confidence: 99%